Observation of CP Violation in Charm Decays; Physical Review Letters; Vol. 122, iss. 21 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Adeva B. Bernardo; Shapkin M. M. Mikhail Mikhaylovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich (2019, 2019)
Title screen